2020
DOI: 10.21037/tau-20-1019
|View full text |Cite
|
Sign up to set email alerts
|

A new risk stratification system of prostate cancer to identify high-risk biochemical recurrence patients

Abstract: Background: Biochemical recurrence (BCR) is considered a decisive risk factor for clinical recurrence and the metastasis of prostate cancer (PCa). Therefore, we developed and validated a signature which could be used to accurately predict BCR risk and aid in the selection of PCa treatments.Methods: A comprehensive genome-wide analysis of data concerning PCa from previous datasets of the Cancer Genome Atlas (TCGA) and the gene expression omnibus (GEO) was performed. Lasso and Cox regression analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Except for MMP11, all of them presented a strong positive correlation with the immune score. To our knowledge, only MMP11 and HAPLN3 have been reported as possible diagnostic biomarkers or prognostic predictors for PCa (22)(23)(24)(25). There is no research on the roles of ARHGAP4 and HAOPLN3 in PCa, but the existing evidence indicates that their functions in tumor recurrence and metastases should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Except for MMP11, all of them presented a strong positive correlation with the immune score. To our knowledge, only MMP11 and HAPLN3 have been reported as possible diagnostic biomarkers or prognostic predictors for PCa (22)(23)(24)(25). There is no research on the roles of ARHGAP4 and HAOPLN3 in PCa, but the existing evidence indicates that their functions in tumor recurrence and metastases should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that PLK1 and KIF4A as biomarkers have a high prognosis value in patients with prostate cancer ( Gao et al, 2018 ; Cao et al, 2020 ; Liu et al, 2020 ; Wu et al, 2020 ; Das et al, 2021 ). PLK1 has been proven to be a potent and promising target for prostate cancer treatment ( Mao et al, 2018 ; Shin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immune response in the tumor immune microenvironment composed of these immune cells, including secretion and cytokines, can greatly affect the balance between tumor progression, tumor clearance and treatment response (11). In addition, increasing research has suggested that cells in the TME have clinicopathological significance in predicting patient prognosis and the therapeutic efficacy of drugs (4,5). In various malignancies, including gastric cancer and glioma, gene signatures from the TME were significantly associated with the outcomes of patients (6,12).…”
Section: Original Articlementioning
confidence: 99%
“…Prostate cancer (PCa) is the most common non-cutaneous malignancy among men and the second leading cause of cancer-related death worldwide (1,2). The prognosis and treatment decisions of PCa are based on the malignant grade using the Gleason score, the clinical stage of the tumor-node-metastasis system (TNM), and serum PSA level (3,4). Despite these well-established clinical predictive and prognostic factors, drastically variable outcomes are observed among PCa patients with similar stages and malignant grades (5).…”
Section: Introductionmentioning
confidence: 99%